Assessment of Quo and Desirable Status of Adult Education Curricula in Elementary and Post-elementary Education - Rezaii, Leila; Assareh, Alireza; Hakimzade, Rezvan; Sedghpour, Bahram Saleh (International Journal of Psychosocial Rehabilitation, 2020)
The overall purpose of this study is to investigate the current and desirable status of adult education curricula in elementary and post-elementary education. In this study, exploratory mixed method was used. In the quantitative section the statistical population was all professors and experts in the field of adult education in the country that 25 people were selected based on theoretical and snowball sampling method. Samples in the qualitative section included all upstream documents related to adult education curriculum and professors, curriculum experts, and adult education that ten people were selected through theoretical sampling (Theoretical) and snowball. The research tool in the qualitative section was semi-structured interview and in the quantitative section a researcher-made questionnaire (based on the qualitative section results). Quantitative data analysis was performed using descriptive and inferential statistics and qualitative data analysis using thematic analysis. The quantitative and qualitative results of the present study showed that twelve components of philosophical foundations, sociological foundations, psychological foundations, political foundations, content, goals, evaluation, teaching and learning strategies, learning time and space, teaching and learning activities, learning materials and teamworking form the cornerstone of the post-elementary curriculum. The results of this study showed that there is a significant difference between the current situation and the desirable status of adult education curricula in elementary and post-primary education.